Impact of Functioning Of Mess on Students Behavior - Dr. Avinash Pal (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Navodaya vidhalaya are residential schools fully funded by Ministry of Education, Govt of India. They have Pan India presence in each and every District of the country.The current study investigates how the JNV school in Jaipur’s trash affects pupils’ conduct. JNV is an experimental Indian school. It aims to educate gifted children better than residential schools by focusing on them. These children are all over the place, even in underprivileged communities. Poor folks don’t have access to good education. Specially gifted or gifted children should have access to top-notch education. The current study project comprises a questionnaire that asks fundamental questions on how the system operates and how students behave. For this project, the school authorities has been contacted directly to gather data, which has been analysed using the t-test and the ANNOVA statistical tool. During data analysis, SPSS and MS-Excel were also used. According to the results of the current study, children are not entirely content with the way that the classroom is organised, and this dissatisfaction has a negative effect on both the students’ mental attitudes and physical health.